2011
DOI: 10.1029/2011jc007219
|View full text |Cite
|
Sign up to set email alerts
|

Can ocean color assimilation improve biogeochemical hindcasts in shelf seas?

Abstract: [1] The objective of this paper is to investigate if the assimilation of ocean color data into a complex marine ecosystem model can improve the hindcast of key biogeochemical variables in shelf seas. A localized Ensemble Kalman filter was used to make a yearlong assimilation of weekly satellite chlorophyll data into a three-dimensional ecosystem model of the western English Channel. The skill of assimilation was evaluated with respect to non assimilated in situ data using twelve time series of biogeochemical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 56 publications
(145 reference statements)
4
95
1
Order By: Relevance
“…Ocean colour data assimilation is being increasingly utilized by the reanalysis and forecasting community (Gehlen et al, 2015), and has already been successfully demonstrated for ERSEM (Ciavatta et al, 2011(Ciavatta et al, , 2014. A suitable ocean colour assimilation scheme for operational purposes is being developed as a collaboration between the Met Office and PML, to be implemented in the SSB ERSEM version and run operationally as part of CMEMS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Ocean colour data assimilation is being increasingly utilized by the reanalysis and forecasting community (Gehlen et al, 2015), and has already been successfully demonstrated for ERSEM (Ciavatta et al, 2011(Ciavatta et al, , 2014. A suitable ocean colour assimilation scheme for operational purposes is being developed as a collaboration between the Met Office and PML, to be implemented in the SSB ERSEM version and run operationally as part of CMEMS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The non-operational POLCOMS-ERSEM system in development at PML and the National Oceanography Centre in Liverpool (NOCL) uses satellite inherent optical properties within ERSEM which has been shown to have a positive impact on the model chlorophyll fields . In the long-term, work is being done to improve the ecosystem model further by including data assimilation of the chlorophyll field from satellite data (Ciavatta et al, 2011) and to include the satellite optical information as used in the POLCOMS-ERSEM system in either NRT or as climatological input for the AMM7-NE system.…”
Section: Discussionmentioning
confidence: 99%
“…Ourmières et al (2009) assimilated nitrate climatology values into a model of the North Atlantic, which improved the model's representation of nitrate compared to the climatology, and led to an improved representation of chlorophyll compared to satellite data. Ciavatta et al (2011) assimilated chlorophyll data into a model of the western English Channel. This resulted in improvements compared to the assimilated data, and also an improved representation of other biogeochemical variables, including a number of plankton functional types and nutrients, compared to independent in situ observations.…”
Section: A Ford Et Al: Assimilating Globcolour Ocean Colour Datamentioning
confidence: 99%